Relationships of intestinal enzymes and serum antitoxin to the pig response to Escherichia coli enterotoxin. - Larivière, S (1975)
The intestinal loop technique was used to evaluate the response of three week old piglets to the heat labile (LT) and the heat stable (ST) enterotoxins produced by Escherichia coli F11(P155). The serum anti-LT activity and the lipase, amylase and trypsin activities in the jejunal lumen of these pigs were determined. Piglets responded independently ti each toxin and no relationship between these responses and serum anti-LT activity or the enzyme activities of the jejunal content could be demonstrated.